EKSTRAKSI KARAGINAN DARI RUMPUT LAUT (Eucheuma spinosum) DENGAN VARIASI SUHU PELARUT DAN WAKTU OPERASI - Risa Sepdwiyanti, Suci Dian Sari, Mohammad Istnaeny Hudha 1) (Jurnal Teknik Kimia, 2012)
One type of seaweed that has good potential and often found in the waters of Indonesia is Eucheuma spinosum (including red algae) which can produce karaginan. Karaginan is a complex mixture from several polysaccharides. In this study, aiming to get the best extraction time and temperature in the product of karaginan from Eucheuma spinosum. Variables used, extraction temperature: 60, 70, 80, 90 (0C) and extraction time: 0.5, 1, 1.5, 2, 2.5 hours. The solvent used, is water and the extraction pH is 8, the ratio of solids solvent: 1: 20 (= 30 g of seaweed: water = 600 mL). From the research results obtained the best persetage of yield at the time 2.5 hours and the temperature 90 ° C, at which in extracted karaginan this condition have yield of 33.0080%. Keywords : Carrageenan, Eucheuma spinosum, Extraction